Differentiated Teaching Strategies for Diverse Learners in Elementary Classrooms: Strategi Pengajaran yang Disesuaikan untuk Siswa Beragam di Kelas Sekolah Dasar - Helda Destiana Sabila Rosyid; Mahardika darmawan kusuma Wardana (Academia Open, 2025)
General Background: Elementary classrooms frequently face learning disparities caused by uniform instructional practices that overlook individual differences. Specific Background: At SD Negeri Larangan, teachers encounter varied student readiness, interests, and learning styles, requiring adaptive classroom approaches. Knowledge Gap: Previous studies often discuss differentiated teaching conceptually, yet limited research documents its concrete implementation in primary school contexts. Aims: This study explores the planning, implementation, and evaluation of teaching strategies applied by a Grade V teacher using a descriptive qualitative design. Results: Data from observation, interviews, and documentation reveal strategies centered on learning style adaptation (visual, auditory, kinesthetic), varied access to materials, creative activities, and individualized guidance, with learning style alignment recorded as the most frequently applied approach and associated with higher student engagement and participation. Novelty: The study provides field-based evidence that links differentiation principles to practical classroom actions across content, process, and product. Implications: Findings offer actionable guidance for teachers and school leaders to design inclusive, responsive, and student-centered instruction in elementary education while supporting policy and professional development planning. Keywords: Differentiated Instruction, Teaching Strategies, Elementary Education, Learning Styles, Qualitative Study Key Findings Highlights: Adaptation to visual, auditory, and kinesthetic preferences dominated classroom practice Creative tasks and flexible material access supported varied participation patterns Individual mentoring addressed heterogeneous readiness levels among pupils